Genetic variation in common cattail (Typha latifolia) in southern Sweden - Fahlgren, David (SLU/Dept. of Plant Breeding (from 130101), 2017)
Typha latifolia and T. angustifolia are wide spread perennial aquatic plants that have long history of being used by humans as a food source (rich in starch) and for raw material but they are not used much today. Typha spp has potential to be used for bioremediation of polluted waste water as they tolerate high amounts of pollutants and are capable of taking up chemical pollutants and heavy metals. They also have some level of tolerance to salinity. Therefore, there is an increased interest in studying them further. And the molecular structure of the starch from in the rhizomes is known. There is a potential use of T. latifolia for production of active carbon. Some experiments with them as substrate for mushroom production have been made. Several microsatellite markers have been developed both for T. latifolia and T. angustifolia that can be used to study genetic variation and crossbreeding between different spp. In this study T. latifolia were collected from 16 different sites in southern Sweden and three different microsatellite markers developed for T. latifolia were used to analyze the genetic variation. The result from the 36 samples collected and analyzed were eight different genotypes, of which five were heterozygotes for one of the markers. But not all samples gave bands and some not for all of the markers used. So, further studies with samples from more locations across Sweden using more markers would be needed to get a more accurate assessment of the genetic variation of T. latifolia in Sweden.